Báo cáo công tác năm 2021 và phương hướng, nhiệm vụ chủ yếu năm 2022 của Ủy ban Thường vụ Quốc hội (Số: 77/BC-UBTVQH15) - Ủy ban Thường vụ Quốc hội (2021)
Toàn văn Báo cáo công tác năm 2021 và phương hướng, nhiệm vụ chủ yếu năm 2022 của Ủy ban Thường vụ Quốc hội (Số: 77/BC-UBTVQH15)